Teaching English to Young Learners in Mexico: Teachers’ Perceptions About Their Teaching Contexts - Tania Millán Librado; Nora M. Basurto Santos (Profile: Issues in Teachers' Professional Development)
This paper discusses the perceptions that six English language teachers, from public schools in the south region of the state of Veracruz in Mexico, have about their particular teaching contexts. A qualitative approach was adopted, and main data collection was through semi-structured interviews. The results show that all teachers have mostly negative perceptions about their teaching conditions. It was concluded that urgent action is needed on the part of the government to improve the English as a foreign language scenario, especially now when the introduction of English as a foreign language has been proposed at even earlier ages in all levels of education in the country.